Effect of NaCl concentration on the performance of sequential anaerobic and aerobic membrane bioreactors treating textile wastewater - Yurtsever, Adem; Calimlioglu, Beste; Gorur, Mesut; Cinar, Ozer; Sahinkaya, Erkan (ELSEVIER SCIENCE SA, 2016)
This study aims at evaluating the performance of sequential anaerobic (AnMBR) and aerobic MBRs (AeMBR) treating synthetic textile wastewater containing varying concentrations (0-1000 mg/L) of NaCl. High COD (up to 90%) and dye (>= 99%) removals were achieved in the AnMBR and increasing salinity did not significantly affect the process performance, although biomass concentrations decreased appreciably in both MBRs. In the AeMBR, although COD remaining in the effluent of the AnMBR was further degraded, dye concentration increased due to autooxidation of aromatic amines. A significant portion of the aromatic amines generated in the AnMBR was also degraded in the AeMBR. Gel permeation chromatography (GPC) analyses illustrated that high molecular weight organics generated in the AnMBR may be entrapped in the gel/cake layer developed on the membrane surface and salinity affected the molecular weight distribution of the organics. Relatively large organic molecules were detected in the external membrane foulants, which may originate from loosely bound EPS. Denaturing gradient gel electrophoresis (DGGE) analysis of 16S rDNA genes showed quite stable community structure in both MBRs. When AnMBR and AeMBR were operated at 4.2 LMH and 8.1 LMH, respectively, MBRs could be operated at low TMPs without any chemical cleaning for long durations. The biogas sparging rate significantly affected cake formation and TMP in the AnMBR. In both MBRs, chemical cleaning almost completely removed irreversible fouling. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anaerobic membrane bioreactor; Aerobic membrane bioreactor; Color removal; Membrane fouling; PILOT-SCALE; AZO-DYE; REACTOR; NANOFILTRATION; WASTEWATERS; FILTRATION; AERATION; TIME; FLUX; Engineering